Annual health checks for people with learning disability. Issue 3 (March 2013) - Maddams, Jessica; Pearson, David
Annual health checks for adults with learning disabilities are now being offered in general practices across the UK, to improve access to mainstream primary healthcare and detection of unmet health needs. This article will cover the rationale behind annual health checks and the evidence regarding the health benefits of comprehensive health checking in this group. We will also summarise the requirements for annual health checks specified in the learning disabilities Directed Enhanced Service (DES) in England, before discussing the barriers to and strategies for undertaking effective health checks in general practice.